ZDHHC5 may regulate the function of NKT cells and the immune response in Meniere’s disease - Ruilong Li; Keguang Chen (Mammalian Genome, 2026)
Meniere’s disease (MD) is a heterogeneous, rare inner ear disorder characterized by recurrent vertigo, fluctuating sensorineural hearing loss, tinnitus, and aural fullness. Its molecular mechanisms remain unclear due to significant clinical and immunological heterogeneity. In this study, we integrated multi‑omics genetic data to systematically screen for palmitoylation regulatory genes associated with MD risk. We first intersected 31 core palmitoylation genes with blood cis‑eQTL datasets to identify candidate expression‑related genes, then performed two‑sample Mendelian randomization (MR) to examine their genetic correlation with MD. Summary‑data‑based MR (SMR) using two independent peripheral blood eQTL cohorts (eQTLGen and GTEx) was further applied to validate robust candidate genes. Two‑sample inverse‑variance weighted (IVW) MR revealed nominally significant associations between PPT2, ZDHHC18, ZDHHC5 and MD risk. Independent SMR validation confirmed that peripheral ZDHHC5 expression was significantly correlated with MD (eQTLGen: PSMR = 0.023; GTEx: PSMR = 0.006), and a non‑significant HEIDI test ruled out strong linkage disequilibrium confounding. We further explored potential immune mediators using a two‑step MR screening framework covering 731 peripheral immune cell phenotypes. After Benjamini–Hochberg false discovery rate (FDR) correction for all immune traits to control for multiple testing, no immune cell phenotype retained an FDR

Apoptotic platelet-mediated tolerogenic vaccine delivery via biomimetic efferocytosis for alleviating acute and chronic colitis - Lu Wang; Junyu Wei; Yemin Xu; Jiapei Gao; Yinhe Xia; Yanqing Zhang; Ruilong Song; Jun Liu; Yuli Li; Gang Chen; Bin Deng (Chemical Engineering Journal, 2026)

Comparative effects of freeze–thaw and FeCl3 conditioning combined with sawdust on sludge dewatering and consolidation - Yajun Wu; Huarui Liu; Xudong Zhang; Yang Liu; Ruilong Li; Zhexin Lin; Châu Nguyễn Xuân Quang (Journal of Water Process Engineering, 2026)

Selective recognition of hydroquinone over catechol on a stacked leaf-like ZnCo/N-doped porous carbon@polymelamine electrode - Yafeng Jin; Didi Tong; Li Qu; Jin Zhang; Fangming Han; Desheng Ma; Ruilong Zhang; Xiangquan Qin; Chen Li (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into synergistic and antagonistic interactions between cationic conditioning agents and freeze-thaw pretreatment for sludge deep dewatering - Yajun Wu; Huarui Liu; Xudong Zhang; Ruilong Li; Zhexin Lin; Vu Quoc Vuong; Châu Nguyễn Xuân Quang (Journal of Environmental Chemical Engineering, 2026)

Coupled effects of water saturation and spatial heterogeneity on CO2 hydrate formation for safe and sustainable carbon storage - Yanfang Li; Tong Zhang; Ming Tang; Ruilong Li; Liang Yuan; Mingchao Wang (Process Safety and Environmental Protection, 2026)

Quasi-periodic signatures of Jupiter’s rotation in the tailside magnetosheath: Observations from Juno and Voyager-2 at ∼100–200 Jupiter radii - Zhonghua Yao; Ruilong Guo; Zhili Zeng; Binzheng Zhang; Jinyan Zhao; Tianran Sun; Wenya Li (Science China Earth Sciences, 2026)
Jupiter has the largest planetary magnetosphere in our solar system, and the rapid planetary rotation imposes a strong centrifugal force on the iogenic plasmas, forming a rotating magnetodisc. An inside-out compression of the magnetopause is expected on the dayside, while in the tail region, the interaction near magnetopause is poorly understood. By comparing particle and wave features near the magnetopause at different distances, we reveal quasi-planetary rotation periodic magnetic depressions in the magnetosheath near the magnetopause at dawnside (local time ∼6 h) at about 100 R J and post-midnight (local time ∼3 h) at about 200 R J . Accompanied by the magnetic depressions, energetic particle enhancements were observed, suggesting acceleration processes on the boundary. The strong magnetic perturbations and energetic particle enhancements are likely consequences of magnetospheric flow compression on the boundary. Particularly, the Voyager 2 observations made at about 200 R J in the tail provide key clues in understanding Jovian magnetotail dynamics and flow circulations.

Construction of human sweat evaporation-analog collagen fiber-based interfacial evaporator by micro‑carbonized fulvic acid photothermal cross-linker - Ruilong Li; Longfang Ren; Yuxing Zhang; Bocheng Qi; Xin Sun; Huaqing Liu; Xiancheng Zhang; Taotao Qiang (Desalination, 2026)

Recyclable high latent heat flexible PEG/EVA phase change composites were constructed via dynamic ion crosslinking networks and applied to enhance the dimensional stability of EVA foam materials - Ruilong Xu; Wei Liu; Yiting Jiang; Shuai Zhao; Lin Li (Chemical Engineering Journal, 2026)

Spin-state engineering via ionic mismatch in MnO2 for high-performance hybrid capacitive deionization - Xiaoke Li; Jinghua Yang; Xuejing Wang; Shiyu Wang; Jingyu Wu; Ruilong Liu; Guixi Wang; Jun Wang; Weikun Ren; Feike Zhang; Weijie Fu; Yingjie Ji; et al. (Desalination, 2026)

Hepatotoxicity of chlorinated organophosphate flame retardants (Cl-OPFRs): a comprehensive review - Xuemeng Wang; Ruilong Li; Wanwan Liu; Mingjie Song; Tao Zeng; Cuili Zhang (Archives of Toxicology, 2026)

Bidirectionally interfacial electronic interactions in Pd/MoS₂ enable efficient formate oxidation through facilitated hydrogen spillover - Feike Zhang; Jun Wang; Guixi Wang; Xiaoke Li; Weikun Ren; Jinghua Yang; Ruilong Liu; Shiyu Wang; Kang Ji; Shuyun Yao; Yingjie Ji; Jingyu Wu; et al. (Chemical Engineering Journal, 2026)

Fishing boats as underestimated vectors for the transmission of high-risk genetic elements in nearshore ecosystems - Zhen Zhao; Yihua Wei; Xinru Pan; Guochao Zhang; Mengyuan Luo; Yijin Wang; Guoqiang Yi; Yanbao Lei; Geng Sun; Ruilong Li (Journal of Hazardous Materials, 2026)

Toxicity evaluation of fosthiazate to Bombyx mori Linnaeus (Lepidoptera: Bombycidae): A new perspective from the chirality - Yuepeng Qiu; Jiyan Hu; Yao Feng; Yan Ma; Chang Li; Yazhu Liu; Yonghong Lai; Changcai Wu; Ruilong Sun; Ting Tang; Lianshan Li; Fengsong Liu (Pesticide Biochemistry and Physiology, 2026)

The anti-oomycete activity and potential mechanisms of pamidronate against development and pathogenicity in Phytophthora sojae - Xina Wu; Xiu Li; Ruilong Wang; Yan Sun; Yang Peng; Xinhang Li; Xinyu Yang (Physiological and Molecular Plant Pathology, 2026)

Edge-attentive graph convolutional network and positive-unlabeled framework for landslide susceptibility mapping - Ruilong Wei; Yamei Li; Yao Li; Zili Wang; Chunhao Wu; Jiao Wang; Bo Zhang; Chengming Ye (Gondwana Research, 2025)

Improving sludge dewaterability through freeze-thaw pretreatment: Ice crystal morphology controls consolidation and rheological enhancement - Yajun Wu; Ruilong Li; Xudong Zhang; Mengze Gao; Vu Quoc Vuong; Châu Nguyễn Xuân Quang (Environmental Research, 2025)

Breaking the flame retardancy-mechanical property dilemma in polypropylene composites with simultaneously imparted high thermal conductivity - Ruilong Li; Yao Chen; Dunan Rao; Xiaolang Chen; Yongzhi Meng; Hong Wu (Chemical Engineering Journal, 2025)

Evolution of deep-seated bedrock landslides in a deep canyon - Yao Li; Zhang Wang; Chenchen Qiu; Ruilong Wei; Jian Guo; Zilong Wu; Nazir Ahmed Bazai; Chengming Ye (Geomorphology, 2025)

CO2 hydrate sequestration in unsealed submarine sediments: A 4D pore-scale experimental investigation - Yanfang Li; Tong Zhang; Liang Yuan; Ming Tang; Ruilong Li; Yongqiang Chen; Wen Luo; Chuanjiu Zhang (Gas Science and Engineering, 2025)

Atomically built-in electric fields in Mn-Ni3S2 catalysts tune antibonding orbital occupancy for accelerated hydrazine oxidation reaction - Guixi Wang; Weikun Ren; Feike Zhang; Kang Ji; Jun Wang; Jinghua Yang; Xiaoke Li; Ruilong Liu; Shiyu Wang; Yingjie Ji; Zhijie Chen; Bing-Jie Ni; et al. (Chemical Engineering Journal, 2025)

The effects and potential mechanisms of statins on growth, development and pathogenicity in Botrytis cinerea - Yang Peng; Xiu Li; Zhen Gao; Ruilong Wang; Xina Wu; Yan Sun; Xinhang Li; Xinyu Yang (World Journal of Microbiology and Biotechnology, 2025)

Self-sensitized brown-TiO2 photocatalyst for highly efficient CO2 reduction under ambient conditions - Cuncun Qian; Ming-Jia Li; Ruilong Wang (Fuel, 2025)

“Using waste straw to prevent pollution”: Enabling closed-loop design of chrome-free tanning agent with tanning-masking dual effect - Huaqing Liu; Taotao Qiang; Ran Zhang; Ruilong Li; Xin Sun; Sijie Yu; Chao Wu; Longfang Ren (Waste Management, 2025)

Emergence of carbapenem resistant Escherichia coli, Morganella morganii, Providencia rettgeri harboring blaNDM genes in minks from China - Asim Munir; Yuetong Lv; Ruilong Song; Xiaoyu Lu; Zhichao Li; Zhiqiang Wang; Ruichao Li (Veterinary Microbiology, 2025)

Topographic stress proxy as a new causative factor in landslide susceptibility mapping - Weilin Kong; Ruilong Wei; Chunhao Wu; Peng Cui; Guoqing Chen; Yifan Zhang; Dongchen Li; Chenxiao Tang (Gondwana Research, 2025)

Increased megafauna stranding risk from sand mining: Lessons from the Yangtze finless porpoise - Ruilong Wang; Qiyue Li; Jiaxian Ren; Yi Han; Xiaodong Sun; Yingen Dai; Yuyin Guo; Kexiong Wang; Ding Wang; Zhigang Mei (Biological Conservation, 2025)

Microbial and Functional Gene Dynamics in Long-Term Fermented Mariculture Sediment - Guochao Zhang; Mengyuan Luo; Cuilian Xu; Xinru Pan; Guoqiang Yi; Wei Xiao; Chenghao Wang; Zhen Zhao; Ruilong Li (Journal of Marine Science and Engineering, 2025)
The microorganisms of mariculture sediments are key to regulating and maintaining their ecosystem balance and have garnered research interest. Although the microbial composition and functional potential of mariculture sediments have been extensively explored in the past, the effects of long-term aquaculture on microbial communities and functional genes have been scarcely studied. Sediment samples from mariculture ponds with durations of 1 year, 6 years, and 10 years were collected in this study. A high-throughput metagenomic analysis was then conducted. The results showed that the sediments fermented for 1 year had the highest α-diversity, creating conditions for the divergence of functional microbial communities. Due to nutrient competition, long-term fermentation led to a decrease in both diversity and functional redundancy. Key functional groups exhibited different temporal succession patterns. In addition, long-term fermentation, especially fermentation over 10 years, resulted in significant differentiation of functional genes, particularly those related to carbon and nitrogen metabolism. This study reveals the distribution pattern of the microbiome during the natural fermentation process and its temporal coupling relationship with the functions of the pond ecosystem. It clarifies the dynamic evolution of functional genes, providing a theoretical basis for the sustainable management of mariculture.

Coupled effects of initial water content with refrigeration temperature and freeze-thaw cycles on dewatering of sludge - Yajun Wu; Ruilong Li; Xudong Zhang; Mengze Gao; Xueke Zang; Châu Nguyễn Xuân Quang (Environmental Research, 2025)

Quaternary gas hydrate dissociation promotes the formation of Shenhu Canyon Group in the South China Sea - Hui Pan; Hui Xie; Zhongxian Zhao; Jinlong Liu; Guozhong Jiang; Ruilong Li; Yuanping Li; Eun Young Lee; Wen Yan (Frontiers in Marine Science, 2025)
The Baiyun deepwater region (Shenhu area) of the Pearl River Mouth Basin (PRMB), northern South China Sea (SCS), is characterized by the presence of abundant gas hydrate deposits and dense submarine canyons. However, the relationships between gas hydrate decomposition and formation of submarine canyons remain unclear. Based on the seismic and well data, the variations of the gas hydrate stability zone (GHSZ) thickness were quantitatively calculated. The results indicate that the thickness of the GSHZ, which ranges from 0 to 350m, is distributed in areas where the water depth exceeds 600m. Since ~2.5 Ma, there have been three combinations of sea level and bottom water temperature (BWT) changes that can significantly reduce the thickness of the GHSZ. These combinations have exerted control over the GHSZ thickness in this region: (1) a slight increase in sea level accompanied by a rapid increase in BWT; (2) a rapid decrease in sea level but a slight decrease in BWT; (3) a rapid increase in both sea level and BWT. It has been found that water depth exerts an influence on the variation of the thickness of GHSZ. The impact in shallow water areas (< 1000m) is more significant than that in deep water areas (> 1000m). Consequently, in the Shenhu area, where the water depth ranges from 500 to 1000 m, the reduction in the thickness of GHSZ is consistently much greater than that in deep water areas. It is hypothesized that during seawater warming or seal level dropping, the substantial decrease in the thickness of GHSZ in the Shenhu area leads to the dissociation of gas hydrates. This dissociation may have triggered methane seepage, resulting in the formation of pockmarks. The pockmarks likely weaken the slope sediments, and the subsequent rapid sea level fall promotes synchronous gravity erosion processes, thereby forming a chain of pockmarks (channel). Continuous gas seepage may further trigger slope failures, which can widen the channel. It is proposed that this iterative process contributes to the formation of the current Shenhu Canyon Group. Our study presents a plausible mechanism elucidating how the reduction in the thickness of GHSZ, the release of methane, and the formation of submarine pockmarks interact to influence and reshape the slope morphology, as well as drive the evolution of submarine canyons. This integrative analysis not only uncovers the complex geological processes at play in the study area but also offers valuable insights into the long term geomorphological development in submarine environments.

An empirical model of the thermospheric winds based on ICON/MIGHTI observations - Rongjin Du; Ruilong Zhang; Libo Liu; Wendong Liu; Wenbo Li; Yuyan Yang; Han Ma; Huijun Le; Yiding Chen (Advances in Space Research, 2025)

In-situ constructing 3D nanocarbon conduction conformal network on silicon anodes for high-performance sulfide-based all-solid-state batteries - Rui Huang; Ruilong Li; Shaobo Li; Wen Yang; Yu Bai; Zhenhua Wang; Kening Sun (Chemical Engineering Journal, 2025)

Hydrodynamic Analysis of Flow Stabilization Process in a Miniature Circulating Water Channel Equipped with Combined Porous Plate Structures - Chengxiang Li; Ruilong Luo; Fang Wang (Journal of Marine Science and Engineering, 2024)
As a foundational platform for fluid dynamics research on underwater devices, the quality of stable and uniform incoming flow in a circulating water channel (CWC) is essential. Due to the inherent structural characteristics of porous media, their application has become widespread in offshore and marine engineering. This study presents the design of a miniature circulating water channel, alongside the development of a computational fluid dynamics (CFD) numerical model to simulate the interaction between porous media and incoming flow. By analyzing the pressure loss of fluid within the porous plates and incorporating it as a source term in the momentum equation, heavy computational costs associated with fine mesh requirements in micro porous models were avoided. Simulations were conducted to investigate the effects of combined porous plates on the flow field, and the porous media model was validated by comparisons with experimental data. The distribution of the flow field within the channel was analyzed to define the test section, which was conducive to further structural optimization. The results indicated that the combined porous plates stabilized the flow field of the CWC, and, following structural optimization, the occurrence of backflow was reduced, thereby expanding the effective test section range.

Rapid detection of microplastics/nanoplastics directly exposed to blood during intravenous injections via mie scattering spectra - Lei Mou; Chuanliu Wu; Ruilong Li; Yaxian Zhu; Guoqiang Su; Yong Zhang (Journal of Hazardous Materials, 2024)

Distinctive patterns of bacterial community succession in the riverine micro-plastisphere in view of biofilm development and ecological niches - Zhen Zhao; Yijin Wang; Yihua Wei; Gen Peng; Tingyu Wei; Jianqiao He; Ruilong Li; Yinghui Wang (Journal of Hazardous Materials, 2024)

Rhizospheric bacterial communities against microplastics (MPs): Novel ecological strategies based on the niche differentiation - Yijin Wang; Zhen Zhao; Meng Jiao; Tiezhu Li; Yihua Wei; Ruilong Li; Gen Peng (Journal of Hazardous Materials, 2024)

A universal adapter in segmentation models for transferable landslide mapping - Ruilong Wei; Yamei Li; Yao Li; Bo Zhang; Jiao Wang; Chunhao Wu; Shunyu Yao; Chengming Ye (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Elucidating the role of double-confined effect in hollow MOFs/GO catalytic membrane for deep arsenic pollution treatment - Jiangdong Dai; Lili Li; Xiaohua Tian; Ruilong Zhang; Dayi Yang; Qiaoyu Gao; Shuting Liu; Jun Zhao; Jian Ye; Xiaobo Zhang; Yi Wang (Desalination, 2024)

Defect engineering induced high metal loading Co-single-atom catalyst on carbon dots for efficient H2O2 electrosynthesis - Ze Lin; Yahui Li; Ruilong Li; Xingen Lin; Bincheng Xu; Zhixuan Chen; Yuen Wu; Ying Wang (Chemical Engineering Journal, 2024)

Correction: Extraction of maize canopy temperature and variation factor analysis based on multi-source unmanned aerial vehicle remote sensing data - Liting Zhai; Wenpan Yang; Changchun Li; Chunyan Ma; Xifang Wu; Ruilong Zhang (Earth Science Informatics, 2024)

Extraction of maize canopy temperature and variation factor analysis based on multi-source unmanned aerial vehicle remote sensing data - Liting Zhai; Wenpan Yang; Changchun Li; Chunyan Ma; Xifang Wu; Ruilong Zhang (Earth Science Informatics, 2024)

Fate and drivers of mariculture-derived microplastics from ponds to mangrove forests - Zhen Zhao; Yihua Wei; Yijin Wang; Gen Peng; Eddy Y. Zeng; Kefu Yu; Xiang-Rong Xu; Ruilong Li (Environmental Pollution, 2024)

Heterogeneous oxidation and adsorption of iodide by Bi-Fe-Mn ternary oxide: Roles of different metal oxide - Nan Wang; Xixi Lv; Ruilong Dai; Ruiping Liu; Yongwang Liu; Li Zhao (Chemical Engineering Journal, 2024)

Lactococcus garvieae as a Novel Pathogen in Cultured Pufferfish (Takifugu obscurus) in China - Ruilong Xu; Zhongning He; Yiyang Deng; Yihao Cen; Zequan Mo; Xueming Dan; Yanwei Li (Fishes, 2024)
In October 2023, a disease outbreak in pufferfish (Takifugu obscurus) farms in Zhongshan City, Guangdong, China, caused high mortality. Diseased fish (mean length: 15 ± 1 cm) exhibited swimming disorders, fin rot, hemorrhage, and an enlarged spleen. Histopathological observations generally revealed inflammation, necrosis, and congestion in the spleen, kidneys, and brain tissues. The most severe pathological changes included interstitial edema and tubular atrophy in the kidneys, hemosiderin deposition in the spleen, massive red blood cell infiltration, and a decrease in lymphocytes. A single strain of bacteria (Tol-1) was isolated from the diseased pufferfish and identified as a Gram-positive streptococcus strain, exhibiting α-hemolysis on sheep blood agar plates. Through biochemical characterization, 16S rDNA sequencing, morphological analysis, and specific primer-based identification, the Tol-1 strain was identified as Lactococcus garvieae, serotype I. Antimicrobial susceptibility testing indicated that Tol-1 was sensitive to Chloramphenicol, Ampicillin, Cephalexin, and Doxycycline, but resistant to Kanamycin, Gentamicin and Ciprofloxacin. In addition, 15 common virulence factors were detected in the Tol-1 strain, including adhPav, adhPsaA, adhC I–II, adh, and hly 1–3. Pufferfish (mean length: 17 ± 1 cm) subjected to artificial infection via intraperitoneal injection (IP) with the Tol-1 strain exhibited clinical symptoms and histopathological damage similar to those observed in naturally infected fish. An infection dose of 1 × 105 CFU/fish resulted in 80% mortality. The study fulfilled Koch’s postulates, indicating that the disease outbreak in pufferfish was caused by L. garvieae, which exhibited a high mortality rate in pufferfish despite the subtle clinical symptoms. These results serve as a warning for pufferfish farming areas and provide a scientific basis for future prevention and control efforts.

Synthesis of biobased Phosphorus-Nitrogen-Silicon ceramizable flame retardant and its flame retardancy effects on EPS - Shuangmei Tan; Xueya Wang; Ruilong Xu; Jiawang Zheng; Xu Zhang; Yutong Li; Wei Liu; Shuai Zhao; Lin Li (Chemical Engineering Journal, 2024)

Travertine deposition rather than tourism activity is the primary contributor to the microplastic risks in alpine karst lakes - Hanyong Zeng; Yijin Wang; Zhen Zhao; Dalin Zhu; Hongxia Xia; Yihua Wei; Peigang Kuang; Dejun An; Ke Chen; Ruilong Li; Yanbao Lei; Geng Sun (Journal of Hazardous Materials, 2024)

Longitude structure of Martian upper atmosphere seen from MAVEN/NGIMS during 2018 Mars dust storm - Wendong Liu; Libo Liu; Zhaopeng Wu; Yiding Chen; Huijun Le; Ruilong Zhang; Wenbo Li; Han Ma; Yuyan Yang (Icarus, 2024)

Weakly hydrophobic microenvironment-assisted membrane-based confined catalysis for efficient organoarsenic contamination removal - Jiangdong Dai; Lili Li; Qihan Fang; Xiaohua Tian; Ruilong Zhang; Jianming Pan; Jun Zhao; Yi Wang; Jian Ye (Chemical Engineering Journal, 2024)

Underwater motion target recognition using artificial lateral line system and artificial neural network method - Ruilong Luo; Chengxiang Li; Fang Wang (Ocean Engineering, 2024)

SIRT1 alleviates Cd nephrotoxicity through NF-κB/p65 deacetylation–mediated pyroptosis in rat renal tubular epithelial cells - Wenxuan Dong; Kanglei Zhang; Xueru Wang; Jiahui Li; Hui Zou; Yan Yuan; Jianhong Gu; Jiaqiao Zhu; Gang Liu; Zongping Liu; Ruilong Song (Science of The Total Environment, 2024)

A powerful method for In Situ and rapid detection of trace nanoplastics in water—Mie scattering - Lei Mou; Qinzhou Zhang; Ruilong Li; Yaxian Zhu; Yong Zhang (Journal of Hazardous Materials, 2024)

Rock and ice avalanche-generated catastrophic debris flow at Chamoli, 7 February 2021: New insights from the geomorphic perspective - Hao Wang; Peng Cui; Yao Li; Jinbo Tang; Ruilong Wei; Anna Yang; Liqin Zhou; Nazir Ahmed Bazai; Guotao Zhang (Geomorphology, 2024)

Experimental study on non-Darcy flow characteristics in conglomerate porous medium - Tong Zhang; Jun Wu; Yongnan Li; Ruilong Li; Ming Tang; Junlin Mao (Acta Geophysica, 2024)

Size effects of microplastics on antibiotic resistome and core microbiome in an urban river - Wenfang Lin; Shaoheng Cao; Qihui Wu; Fei Xu; Ruilong Li; Li Cui (Science of The Total Environment, 2024)

Design and motion characteristics analysis of underwater biomimetic jellyfish based on shape memory alloy springs - Ruilong Luo; Shuai Li; Fang Wang (Ocean Engineering, 2024)

Secreted salt and hydrodynamic factors combine to affect dynamic fluctuations of microplastics on mangrove leaves - Yihua Wei; Meng Jiao; Zhen Zhao; Liangdong Tang; Yijin Wang; Jun Deng; Gen Peng; Ruilong Li; Yinghui Wang (Journal of Hazardous Materials, 2024)

A quantitative analysis of latitudinal variation of ionospheric total electron content and comparison with IRI-2020 over China - Yuyan Yang; Libo Liu; Xiukuan Zhao; Tingwei Han; M. Arslan Tariq; Yiding Chen; Hui Zhang; Huijun Le; Ruilong Zhang; Wenbo Li; Wenjie Sun; Guozhu Li (Advances in Space Research, 2024)

Insight into the role of niche concept in deciphering the ecological drivers of MPs-associated bacterial communities in mangrove forest - Yijin Wang; Meng Jiao; Zhen Zhao; Yinghui Wang; Tiezhu Li; Yihua Wei; Ruilong Li; Fei Yang (Water Research, 2024)

Construction of fulvic acid-based chrome-free tanning agent with on-demand regulation and wastewater recycling: A novel tanning-dyeing integrated strategy - Ruilong Li; Longfang Ren; Sijie yu; Huaqing Liu; Xin Sun; Taotao Qiang (Chemical Engineering Journal, 2024)

Dynamic fluctuations in plant leaf interception of airborne microplastics - Meng Jiao; Yijin Wang; Fei Yang; Zhen Zhao; Yihua Wei; Ruilong Li; Yinghui Wang (Science of The Total Environment, 2024)

Tianwen-1 and MAVEN observations of Martian oxygen ion plumes - Xiao Ma; Anmin Tian; Ruilong Guo; Lihui Chai; Quanqi Shi; Shichen Bai; Qiugang Zong; Linggao Kong; Wenya Li; Binbin Tang; Aibing Zhang; Suiyan Fu; et al. (Icarus, 2023)

Distinct microplastics abundance variation in root-associated sediments revealed the underestimation of mangrove microplastics pollution - Tiezhu Li; Yijin Wang; Meng Jiao; Zhen Zhao; Ruilong Li; Chengrong Qin (Science of The Total Environment, 2023)

Quantifying health risks of plastisphere antibiotic resistome and deciphering driving mechanisms in an urbanizing watershed - Longji Zhu; Ruilong Li; Kai Yang; Fei Xu; Chenshuo Lin; Qinglin Chen; Dong Zhu; Qian Sun; Yong-Guan Zhu; Li Cui (Water Research, 2023)

VPS41-mediated incomplete autophagy aggravates cadmium-induced apoptosis in mouse hepatocytes - Tao Wang; Lianqi Yan; Li Wang; Jian Sun; Huayi Qu; Yonggang Ma; Ruilong Song; Xishuai Tong; Jiaqiao Zhu; Yan Yuan; Jianhong Gu; Jianchun Bian; et al. (Journal of Hazardous Materials, 2023)

Selective enrichments for color microplastics loading of marine lipophilic phycotoxins - Ruilong Li; Jiuming Wang; Jun Deng; Gen Peng; Yijin Wang; Tiezhu Li; Beibei Liu; Yong Zhang (Journal of Hazardous Materials, 2023)

Al3+ intercalated NH4V4O10 nanosheet on carbon cloth for high-performance aqueous zinc-ion batteries - Ke Wang; Ruilong Yuan; Mengjun Li; Ying Huang; Wei Ai; Zhuzhu Du; Pan He; Binwu Wang (Chemical Engineering Journal, 2023)

Hollow BiOI/Bi5O7I hierarchical microsphere with S-scheme heterostructure for efficiently removal of tetracycline hydrochloride - Junhui Yi; Runkun Xie; Ruilong Liu; Minghao Li; Haoxian Zeng; Qingqing Chen; Linxuan Cai; Ning Li; Changlin Yu; Zhenghui Liu; Dehao Li (Journal of Water Process Engineering, 2023)

Role of mangrove forest in interception of microplastics (MPs): Challenges, progress, and prospects - Yijin Wang; Meng Jiao; Tiezhu Li; Ruilong Li; Beibei Liu (Journal of Hazardous Materials, 2023)

Occurrence and distribution of lipophilic marine algal toxins in the coastal seawater of Southeast China and the South China Sea - Jiuming Wang; Ruilong Li; Beibei Liu; Qinzhou Zhang; Xiang Wang; Yaxian Zhu; Yong Zhang (Marine Pollution Bulletin, 2023)

N-acetylcysteine delayed cadmium-induced chronic kidney injury by activating the sirtuin 1–P53 signaling pathway - Wenxuan Dong; Kanglei Zhang; Zhonggui Gong; Tongwang Luo; Jiahui Li; Xueru Wang; Hui Zou; Ruilong Song; Jiaqiao Zhu; Yonggang Ma; Gang Liu; Zongping Liu (Chemico-Biological Interactions, 2023)

(±) Erysectin A, a new isoprenylated isoflavone with a rare acetonyl group from Erythrina secundiflora Hassk - Ruilong Luo; Fengqiu Li; Hongdan Zhuang; Liqin Wang (Natural Product Research, 2022)

Metal contamination in soils and windowsill dusts: implication of multiple sources on dust metal accumulation within a city affected by Pb smelting - Weiqin Xing; Jie Luo; James A. Ippolito; Ruilong Lu; Zhongyu Hao; Liping Li (Environmental Science and Pollution Research, 2022)

An attention-constrained neural network with overall cognition for landslide spatial prediction - Ruilong Wei; Chengming Ye; Yonggang Ge; Yao Li (Landslides, 2022)

Novel IBA57 mutations in two chinese patients and literature review of multiple mitochondrial dysfunction syndrome - Feixia Zhan; Xiaoli Liu; Ruilong Ni; Taotao Liu; Yuwen Cao; Jingying Wu; Wotu Tian; Xinghua Luan; Li Cao (Metabolic Brain Disease, 2022)

Geochemistry of gold deposits in the Zhangbaling Tectonic Belt, Anhui province, China - Dezhi Huang; Xianying Wang; Xiaoyong Yang; Guoming Li; Shiqi Huang; Zhen Liu; Zehua Peng; Ruilong Qiu (International Geology Review, 2011)